A centralidade da Palavra de Deus em Lucas 5,1-11 (The centrality of the Word od God in Luke 5,1-11) - DOI: 10.5752/P.2175-5841.2013v11n30p682 - Perondi, Ildo (Horizonte, 2013)
The scholars haven’t given too much attention to the function of the Word of God in the report of the miraculous catch of fish in Luke, at the literary and theological level. Thus, the objective of this paper was to analyze the pericope of Luke 5:1-11, with emphasis on the Word of God proclaimed in Jesus and through Him. The methodology used was the analysis and interpretation of texts, focusing on the historical-critical method and its essential elements, besides the use of other methods, based on the science of language. It’s possible to say that the Word of God occupies a central place in the plot, giving cadence to the report and elucidating the theological sense that Luke wanted to print, which is evidenced by the changes he has made in the original report. In the pericope of the miraculous catch of fish, the Word is proclaimed by Jesus in a performative way; it makes the miracle happen, leads Peter to conversion and gives him a new mission. In Luke's theology, one hears the echo of primitive communities, born around the word of the Lord.